Efficacy and safety of addition of bevacizumab to FOLFIRI or irinotecan/bolus 5-FU/LV (IFL) in patients with metastatic colorectal cancer: A meta-analysis. Issue 46 (November 2016) - Chen, Ke; Gong, Yinya; Zhang, Qi; Shen, Yanping; Zhou, Taoqi
Abstract : Abstract: Recent studies have paid much attention on the safety of bevacizumab as adjuvant chemotherapy for metastatic colorectal cancer. The aim of this meta-analysis was to study the efficacy and safety of bevacizumab in combination with irinotecan, bolus followed by infusional 5-fluorouracil, and leucovorin (FOLFIRI) and, irinotecan, bolus fluorouracil, leucovorin (IFL) for patients with metastatic colorectal cancer (mCRC). An electronic search of related trials was conducted from PubMed, EMBASE, Cochrane Library databases. Risk ratio (RRs) and its 95% confidence intervals (95% CIs) were calculated by using either DerSimonian–Laird method or Mantel–Haenszel method according to the heterogeneity of included articles. The risk of mortality, therapeutic efficacy, and adverse effect were meta-analyzed. In total, 6 RCTs including 2165 participants (1109 in the treatment group, 1056 in the control group) were included in this meta-analysis. Compared with FOLFIRI-panitumumab/cetuximab, the bevacizumab addition significantly reduced the complete response (CR) rate (RR [95%CI] = 0.31[0.11, 0.89], P = 0.03) and the risk of grade 3/4 adverse event (RR [95%CI] = 0.89[0.80, 0.98], P = 0.01). Compared with FOLFIRI and IFL alone, the addition of bevacizumb significantly increased the partial response (PR) and objective response (OR) rates. Compared with IFL alone, the addition of bevacizumb significantly reduced the mortality risk of PFS (RR [95%CI] = 0.53[0.42, 0.66], P < 0.00001) and OS (RR[95%CI] = 0.70[0.60, 0.82], P < 0.00001), but increased the risk of adverse events (RR[95%CI] = 1.14[1.06, 1.21], P = 0.0002). Combination chemotherapy of bevacizumab plus FOLFIRI or IFL had a relative high efficacy and acceptable safety for treatment of mCRC.